Engineering design of outer‐selective tribore hollow fiber membranes for forward osmosis and oil‐water separation. Issue 12 (25th August 2015) - Li, Xue; Ang, Wan Lin; Liu, Yingda; Chung, Tai‐Shung
Abstract : Outer‐selective thin‐film composite (TFC) hollow fiber membranes offer advantages like less fiber blockage in the feed stream and high packing density for industrial applications. However, outer‐selective TFC hollow fiber membranes are rarely commercially available due to the lack of effective ways to remove residual reactants from fiber's outer surface during interfacial polymerization and form a defect‐free polyamide film. A new simplified method to fabricate outer‐selective TFC membranes on tribore hollow fiber substrates is reported. Mechanically robust tribore hollow fiber substrates containing three circular‐sector channels were first prepared by spinning a P84/ethylene glycol mixed dope solution with delayed demixing at the fiber lumen. The thin wall tribore hollow fibers have a large pure water permeability up to 300 L m −2 h −1 bar −1 . Outer‐selective TFC tribore hollow fiber membranes were then fabricated by interfacial polymerization with the aid of vacuum sucking to ensure the TFC layer well‐attached to the substrate. Under forward osmosis studies, the TFC tribore hollow fiber membrane exhibits a good water flux and a small flux difference between active‐to‐draw (i.e., the active layer facing the draw solution) and active‐to‐feed (i.e., the active layer facing the feed solution) modes due to the small internal concentration polarization. A hyperbranched polyglycerol was further grafted on top of the newly developed TFC tribore hollow fiber membranes for oily wastewater treatment. The membrane displays low fouling propensity and can fully recover its water flux after a simple 20‐min water wash at 0.5 bar from its lumen side, which makes the membrane preferentially suitable for oil‐water separation. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4491–4501, 2015